1996
DOI: 10.1523/jneurosci.16-16-05196.1996
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Activity in Locus Coeruleus Results from Dendritic Interactions in Pericoerulear Regions

Abstract: Locus coeruleus (LC) neurons in brain slices from adult rats were studied using intracellular and extracellular recordings to investigate synchronous activity. Spontaneous field potentials were recorded with extracellular electrodes in solutions containing tetraethylammonium chloride (10 mM) and BaCl 2 (1 mM). These field potentials were found throughout but not outside the LC cell body region. No field potentials were observed in control solutions. Paired recordings showed that field potentials were synchrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
1
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(165 citation statements)
references
References 37 publications
12
150
1
2
Order By: Relevance
“…Further, in a recent report, Rekling et al (2000) found that Ն20 -30 min of exposure to 100 M CBX reduced input resistance as well as the number of action potentials elicited by depolarizing current in presumptive rhythmogenic type-1 preBötC neurons of neonatal mice. In contrast to this report, exposure to 100 M CBX has also been demonstrated to be ineffective in altering the resting conductance, action potential waveform, spontaneous firing, and evoked action potentials in locus coeruleus neurons of both neonatal and adult rats (Dean et al 2001;Ishimatsu and Williams 1996;Travagli et al 1995). We believe that the results of our experiments were mediated by blockade of gap junctions and not by nonspecific effects because both glycyrrhetinic acid derivatives and higher-order alcohol gap junction inhibitors (i.e., 2 classes of chemically distinct gap junction blockers) elicited similar modulation of phrenic nerve discharge, the concentrations of the gap junction blockers used were generally lower than those known to cause nonspecific effects, and the control agents (i.e., GZA and hexanol) employed were ineffective in altering phrenic nerve discharge in a manner similar to that observed by application of uncoupling agents.…”
Section: Gap Junction Uncoupling Agentscontrasting
confidence: 90%
See 2 more Smart Citations
“…Further, in a recent report, Rekling et al (2000) found that Ն20 -30 min of exposure to 100 M CBX reduced input resistance as well as the number of action potentials elicited by depolarizing current in presumptive rhythmogenic type-1 preBötC neurons of neonatal mice. In contrast to this report, exposure to 100 M CBX has also been demonstrated to be ineffective in altering the resting conductance, action potential waveform, spontaneous firing, and evoked action potentials in locus coeruleus neurons of both neonatal and adult rats (Dean et al 2001;Ishimatsu and Williams 1996;Travagli et al 1995). We believe that the results of our experiments were mediated by blockade of gap junctions and not by nonspecific effects because both glycyrrhetinic acid derivatives and higher-order alcohol gap junction inhibitors (i.e., 2 classes of chemically distinct gap junction blockers) elicited similar modulation of phrenic nerve discharge, the concentrations of the gap junction blockers used were generally lower than those known to cause nonspecific effects, and the control agents (i.e., GZA and hexanol) employed were ineffective in altering phrenic nerve discharge in a manner similar to that observed by application of uncoupling agents.…”
Section: Gap Junction Uncoupling Agentscontrasting
confidence: 90%
“…For example, both electrotonic and anatomical (dye-and/or tracer-) coupling, which occur via gap junctions, have been demonstrated in multiple respiratory-related brain stem regions between some populations of neurons (and/or astrocytes) in preparations obtained from embryonic and early postnatal rodents (for a recent review, see Solomon and Dean 2002). Similar findings, however, have yet to be demonstrated in these regions in preparations obtained from adult rodents with the exception of the locus coeruleus, which typically requires the addition of BaCl 2 , tetraethylammonium chloride (TEA), and tetrodotoxin (TTX) to the superfusate (Dean et al 2001;Ishimatsu and Williams 1996;Travagli et al 1995). Thus differences in coupling strength between electrically coupled neurons in an oscillatory or rhythmic network (i.e., respiratory network) may account for the differences, at least in part, observed between our current findings in the adult rodent and those of Rekling et al (2000) and Bou-Flores and Berger (2001) in the early neonatal rodent.…”
Section: Role Of Gap Junctions In Inspiratory Motor Activity: Neonatamentioning
confidence: 88%
See 1 more Smart Citation
“…It has been noted that electrical coupling between activated LC neurons would result in the synchronized release of norepinephrine in most, if not all, projection areas of the LC (Christie et al, 1989;Travagli et al, 1995;Ishimatsu and Williams, 1996). Coordinated release of norepinephrine at many LC target sites would be consistent with the presumed ability for the LC to simultaneously influence broad areas of brain in the behavioral functions of this nucleus.…”
Section: Functional Implications Of Lc Neuronal Coupling and Gap Juncmentioning
confidence: 94%
“…In addition, synchronous electrical activity of LC neurons has been observed in slices from adult rats under conditions that indirectly support mediation of this activity by gap junctional coupling (Travagli et al, 1995;Ishimatsu and Williams, 1996;Alvarez et al, 2002). In vivo, synchronized LC neuronal activity may have functional impact by promoting synchronous release of norepinephrine throughout the widespread projection areas of the LC, which is thought to contribute to overall cognitive performance, learning and memory (Ashton-Jones andCohen, 2005,2006).…”
mentioning
confidence: 99%